A 3-year retrospective study of 866 children and adolescent outpatients followed in the Nice Pediatric Psychotrauma Center created after the 2016 mass terror attack - Gindt, Morgane; Fernandez, Arnaud; Zeghari, Radia; Ménard, Marie-Line; Nachon, Ophelie; Richez, Aurélien; Auby, Philippe; Battista, Michele; Askenazy, Florence (Frontiers in Psychiatry, 2022)
Background The mass terrorist attack in Nice, France, in July 2016 caused deaths and injuries in a local population, including children and adolescents. The Nice Pediatric Psychotrauma Center (NPPC) was opened to provide mental health care to the pediatric population (0–18 years) who experienced traumatic events. Objectives This study describes the specificity of the care pathway for young trauma victims, with an explanation of how the NPPC works during the first three years. Methods In this retrospective study, we conducted quantitative and qualitative data collection about new and follow-up consultations, primary and comorbid diagnoses, and the kind of trauma (terrorist attack versus other kinds of trauma). Ethics approval was obtained from the local Ethics committee. Results 866 children and adolescents were followed in the NPPC. We found a high rate of Post-Traumatic Stress Disorder (PTSD; 71%) in this population with a high rate of comorbidities (67%), mainly sleep disorders (34.7%) and mood and anxiety disorders (16.2%). A high number of children and adolescents impacted by the terrorist attack required follow-up consultations after exposure to the mass terrorist attack, the first care-seeking requests continued to occur three years later, although at a slower rate than in the first and second years. New consultations for other kinds of trauma were observed over time. Discussion This study supports previous findings on the significant impact of mass trauma in the pediatric population showing even a higher level of PTSD and a high rate of comorbidities. This may be explained by the brutality of the traumatic event, particularly for this age group. The findings of this study have implications for early interventions and long-term care for children and adolescents to prevent the development of chronic PTSD into adulthood.